2022
DOI: 10.2903/sp.efsa.2022.en-7792
|View full text |Cite
|
Sign up to set email alerts
|

Literature review on the main existing structures and systematic/academic initiatives for surveillance in the EU for zoonoses in the environment and the methods for surveillance of pathogens in the environment

Abstract: A small proportion of disease surveillance programs target environment compartment, and in the EU these are restricted to few countries. The present report is composed of two literature reviews (i) on the main existing structures and systematic/academic initiatives for surveillance in the EU for zoonoses in the environment, and (ii) on the methods for pathogen surveillance in the environment. Concerning (i), it is noteworthy that the most frequently reported objective was to evaluate control and eradication st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 184 publications
0
4
0
Order By: Relevance
“…Furthermore, recent reports by the ENETWILD‐consortium (2022a, b) described and mapped the main existing structures and systematic initiatives, for surveillance of zoonoses (transboundary, emerging and re‐emerging) in domestic animals and wildlife in the EU. The analysis of a questionnaire distributed to MSs about official surveillance programmes ( ENETWILD ‐consortium et al, 2022c) revealed that the integration between sectors is not generalised, which is a necessary step to develop OH surveillance for multi‐host transboundary zoonotic pathogens.…”
Section: Assessment Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent reports by the ENETWILD‐consortium (2022a, b) described and mapped the main existing structures and systematic initiatives, for surveillance of zoonoses (transboundary, emerging and re‐emerging) in domestic animals and wildlife in the EU. The analysis of a questionnaire distributed to MSs about official surveillance programmes ( ENETWILD ‐consortium et al, 2022c) revealed that the integration between sectors is not generalised, which is a necessary step to develop OH surveillance for multi‐host transboundary zoonotic pathogens.…”
Section: Assessment Resultsmentioning
confidence: 99%
“…The Enetwild consortium has carried out literature reviews on worldwide surveillance systems targeting transboundary zoonotic and emerging diseases within the holistic One‐Health perspective (Enetwild consortium et al, 2022a), and on the main existing structures and systematic/academic initiatives for surveillance in the EU for zoonoses in the environment and the methods for surveillance of pathogens in the environment (Enetwild consortium et al, 2022b), which were consulted by the Working Group (WG) during the assessment process.…”
Section: Data and Methodologiesmentioning
confidence: 99%
“…16 Alves et al observations provide a modern perspective on sensor technology for zoonotic diseases in Europe, with an emphasis on research done in Portugal. 87 In the European context, biosensors can be utilized to detect zoonotic illnesses.…”
Section: Role Of Biosensors In the Detection Of Zoonotic Pathogensmentioning
confidence: 99%
“…The survey of elusive species, such as the brown bear, has largely been favored by the development of non-invasive genetic material monitoring, such as feces or sponges [ [17] , [18] , [19] , [20] , [21] ], without the need to capture or disturb them [ 18 ]. This sampling approach allows to explore ecosystem-level processes such as host-pathogen relationships, making possible the early detection of pathogens and the identification of hotspots for disease transmission [ 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%